Removal of Iron (Fe) by adsorption using activated Carbon Moringa oleifera (ACMO) in aqueous solution / Nurul Zawani Alias et al. - Alias, Nurul Zawani; Mohamad Zuki, Noor Aina; Alias, Siti Hajar; Kamal, Mohd Lias (Universiti Teknologi MARA, Perlis, 2012)
Activated carbon has been widely developed as an adsorbent to adsorb heavy metal in wastewater due to its high efficiency and low cost. Activated carbon of Moringa oleifera (ACMO) was prepared from the woods for the removal of iron in aqueous solution. The ACMO was produced using chemical activation process impregnation with phosphoric acid as the activating agent. The surface morphology of ACMO was characterized using SEM, and the functional group present was determined using FTIR. Effects of various operating variables namely the carbon dose, adsorbate concentration and contact time on the removal of iron ions have been studied. The adsorption capacity was determined as a function of carbon doses (0.1, 0.2, 0.3, 0.4 and 0.5 g), adsorbate concentration (2, 4, 6, 8 and 10 mg/L) and the contact time between ACMO and aqueous solution (30, 60, 90 and 120 min) with constant parameters of temperature 303 K, agitation at 180 rpm and pH 8. From the data obtained, percent of moisture present in ACMO and raw M. oleifera (RMO) were 6.752% and 9.512% respectively. Meanwhile, amount of ash in ACMO was 1.451% and in RMO was 7.592%. In addition, the volatile matter present in ACMO was replaced from RMO about 28.431% and 23.715% respectively. The percentage of fixed carbon of ACMO and RMO were 63.366% and 59.181% respectively. The highest adsorption capacity obtained was at 8.043 mg/g with the amount of carbon dosage of 0.1 g, concentration of iron solution of 10 mg/L and contact time of 120 min.